Kedewasaan Rohani Dalam Efesus 4:11-16 dan Implikasinya bagi Penginjilan Pribadi: Kajian Eksegetis dan Teologi Praktis - Sunarti Sunarti (Shift Key : Jurnal Teologi dan Pelayanan, 2026)
This study is based on the reality that many believers experience spiritual immaturity, which is characterized by a lack of courage in proclaiming the Gospel. Therefore, a theological understanding is needed to affirm that spiritual maturity is closely related to the urgency of personal evangelism as a tangible expression of faith growth. Academically, this study aims to contribute to Pauline theology by emphasizing the relationship between spiritual maturity and personal evangelism. This approach demonstrates that Paul’s spirituality cannot be separated from the aspects of mission and ecclesiology. This research employs a biblical literature study method that relies not only on primary data in the form of biblical texts, but also on secondary data from biblical literature and Pauline theology, including commentaries, systematic theology works, scholarly articles, and theological journals discussing the concepts of spiritual maturity and evangelism. Through theological and biblical analysis, this study seeks to demonstrate that personal evangelism is not merely a ministry activity, but an integral part of spiritual maturity in Christ. Practically, the findings of this study provide a theological foundation for the church to make discipleship the basis of evangelism.